2020
DOI: 10.21511/ppm.18(4).2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Public servants’ perception of leadership style and its impact on organizational commitment

Abstract: Lebanon is facing an unprecedented political and economic crisis. Consequently, the country now urgently needs more than ever committed public managers, more involved and more effective in their work responsibilities to enhance public sector performance and reduce the consequences of the crisis. Little research has been done on the role of leadership in promoting organizational commitment in the public sector in Lebanon. Thus, referring to the leadership full range theory, this study aims to investigate the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Equally, there are also previously conducted studies that all resulted in positive and negative relationships of this specific style of commitment. On the positive results, findings revealed the positive association of laissez-faire style to other factors, most especially the commitment of individuals in an organization (Amini et al, 2019;Dim & Nzube, 2020;Harb et al, 2020;Lanier, 2020). On the contrary, various findings revealed that there is a negative association between laissez-faire to commitment (Ekpenyong, 2020;Maroof Khan, 2021;Nweke et al, 2021;Robert & Vandenberghe, 2021).…”
Section: Laissez-faire Leadership Style and Commitmentmentioning
confidence: 99%
“…Equally, there are also previously conducted studies that all resulted in positive and negative relationships of this specific style of commitment. On the positive results, findings revealed the positive association of laissez-faire style to other factors, most especially the commitment of individuals in an organization (Amini et al, 2019;Dim & Nzube, 2020;Harb et al, 2020;Lanier, 2020). On the contrary, various findings revealed that there is a negative association between laissez-faire to commitment (Ekpenyong, 2020;Maroof Khan, 2021;Nweke et al, 2021;Robert & Vandenberghe, 2021).…”
Section: Laissez-faire Leadership Style and Commitmentmentioning
confidence: 99%
“…On the other hand, when the level of commitment is high, communication is good and so is decision quality [8]. We urgently need public managers who are more committed than ever, more involved than ever, and more effective in their work responsibilities to improve the public sector performance than ever [9]. Having a high level of commitment results in good performance and wise decision making which leads to the achievement of sustainable development [10].…”
Section: Introductionmentioning
confidence: 99%